The Failure in the Surveillance of the Security Mechanisms in the Importation of Vehicles and its Incidence in the Responsibility of the State - Ulrich Astaiza, William Eugene (DIXI, 2021)
Objective: To determine the responsibility of the Colombian State for the failure in service due to the importation of vehicles that do not comply with quality standards. In addition, it seeks to establish that the current regulations on vehicle safety propose criteria of distinction that are unsustainable in a Social State under the rule of law. Methodology: The methodology used was the systematic review of bibliographic, jurisprudential and legal sources, and the request through petitions to the corresponding entities (MinCyT, Dian, MinTransporte). Once the information was analyzed and systematized, the interpretation and construction of this text was carried out. Conclusions: The responsibility of the State is compromised with those vehicles that circulate without the safety measures established in Resolution 3752 of 2015, given that although this rule is not retroactive, it does evidence that the State is not able to protect all Colombians in their life, honor and property, and that it is because of this that the failure in the safety measures in imports has allowed unsafe vehicles such as cabs without storage and without dual airbags, abs brakes or headrests to circulate through the cities without any kind of control to their safety.